Effects of an integrative neuromuscular training protocol vs. FIFA 11+ on sprint, change of direction performance and inter-limb asymmetries in young soccer players - Arede, J.; Fernandes, J.; Moran, J.; Leite, N.; Romero-Rodriguez, D.; Madruga-Parera, M. (International Journal of Sports Science & Coaching, 2022)
This study compared the effects of integrative neuromuscular training (INT) versus FIFA 11+ protocols on sprint, change of direction performance and inter-limb asymmetries. Thirty young (U-11) male soccer players (age: 11.2±0.7years; height: 145.6±6.8cm; body mass: 72.5±3.0kg) were randomly assigned to each training group, which consisted of two sessions/week for a period of 6-weeks. The INT consisted of play-based tasks designed according to structured training principles, whereas the FIFA 11+ followed standard procedures. Before and after the intervention, 0-20 sprint time and double 180° change of direction test were measured from which change of direction deficit and inter-limb asymmetries were also computed. Significant improvements were found in double 180° change of direction test and deficit for both legs in both groups (all p<0.01). A significant decrease was observed in 0-20 sprint time (p<0.05), and inter-limb asymmetries for FIFA 11+ group. A significant group-by-time effect, which favored the FIFA 11+ group, was observed on double 180° change of direction in right leg (F=15.08, p<0.01, 2p=0.35), but also in change of direction deficit in right (F=214.19, p<0.01, 2p=0.88), and left legs (F=126.79, p<0.01, 2p=0.82). These findings suggest youth soccer practitioners should select the FIFA 11+ program to improve inter-limb asymmetries and 0-20 sprint time, and that both training methods are suitable to improve 180° change of direction performance.